2021
DOI: 10.3390/cells10020213
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Human Zip (SLC39) Zinc Transporters in Saccharomyces cerevisiae for Biophysical Characterization

Abstract: Zinc constitutes the second most abundant transition metal in the human body, and it is implicated in numerous cellular processes, including cell division, DNA and protein synthesis as well as for the catalytic activity of many enzymes. Two major membrane protein families facilitate zinc homeostasis in the animal kingdom, i.e., Zrt/Irt-like proteins (ZIPs aka solute carrier 39, SLC39, family) and Zn transporters (ZnTs), essentially conducting zinc flux in the opposite directions. Human ZIPs (hZIPs) regulate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…6 A , top). This likely is a dimer; experiments with recombinant ZIP proteins have demonstrated that both monomer and dimer forms are detected in denaturing gels like those used here ( 40 ).
Figure 6 CaCl 2 treatment increases cell surface residence of ZIP8 and ZIP14 in hBMVECs.
…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…6 A , top). This likely is a dimer; experiments with recombinant ZIP proteins have demonstrated that both monomer and dimer forms are detected in denaturing gels like those used here ( 40 ).
Figure 6 CaCl 2 treatment increases cell surface residence of ZIP8 and ZIP14 in hBMVECs.
…”
Section: Resultsmentioning
confidence: 69%
“…6A, top). This likely is a dimer; experiments with recombinant ZIP proteins have demonstrated that both monomer and dimer forms are detected in denaturing gels like those used here (40).…”
Section: Intracellular Ca 2+ Regulates the Surface Presentation Of Zi...mentioning
confidence: 63%
See 1 more Smart Citation
“…We also hoped that the application of not just a single metabolomics platform, but cross omics technologies coupled with big-data analytics would help explain these gaps and providing new and vital targets in the finetune of autophagy processes following nutritional deprivations. The discovery of new metabolic (by)products, and by extension the pathways that are being regulated, provides potential intervention targets as predictive roles for studies such as cancer [30] as well as neurodegenerative diseases [52] of which autophagy is implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Baker's yeast Saccharomyces cerevisiae has been used as research models for diseases such as neurodegenerative disorders [22], aging [23], lifespan [24] oxidative stress [25], and autophagy [26]. The genes in S. cerevisiae are highly homologous to those in humans [27,28], and the simplicity of manipulating the genes [14,29,30] and nutrition [31,32] of this shortlived yeast make it a favorable eukaryotic representative. Autophagy defective mutant, atg1 was first discovered in S. cerevisiae, and through this led to the discoveries of other ATG related genes that are involved in the autophagy following starvation [33].…”
Section: Introductionmentioning
confidence: 99%